Establishment of porosity and permeability models correlation to validate E.coli Transport to ground water aquifers: Rivers state of Nigeria - Eluozo, Solomon Ndubuisi; Ademiluyi, J. O. (International Journal of Engineering and Technology, 2012)
The evaluation of porosity and permeability models correlation on the migration of e.coli transport in deltaic environment has been assessed.  This is to validate the model generated from the experimental analysis in the study location, this model are generated through the experimental results  from both parameters, the theoretical values from  both parameters  confirm that the models generated is a bench mark that can  be applied as a  design criteria  in preventing the migration of e.coli to ground water aquifer, it has also  confirm that it plays a major role in fast transport of e.coli in deltaic environment, the figures displayed shows the level of deposition of geological formation in the study area, the study has also explain the migration of the microbes influenced by porosity and permeability,  the results from the experiment that generated  theoretical values for porosity and permeability  were evaluated to see their relationship  in terms of influence on the behaviour of the microbial transport as a system known as plug flow.  the results   has been  confirm that without any inhibition from any other deposition,  e.coli  will be in progressive phase condition, therefore it is advise that the models generated from the study area should be applied in design of bore hole in other to prevent the pollution emanating from e.coli in the study area, finally the relationships verified from the study has  a fit  to the existing geological history of the study area that  is predominant of alluvium deposition, this condition ascertain the reality of the experimental results generated from the study area ,it should be applied  to avoid water related diseases  and the threat of life